2016
DOI: 10.12717/dr.2016.20.1.023
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Light Spectra to Growth of the Rearing Tiger Puffer Takifugu rubripes

Abstract: In fish, light (photoperiod, intensity and spectra) is main regulator in many physiological actions includinggrowth. We investigate the effect of light spectra on the somatic growth and growth-related gene expression in the rearing tiger puffer. Fish was reared under different light spectra (blue, green and red) for 8 weeks. Fish body weight and total length were promoted when reared under green light condition than red light condition. Expression of somatostatins (ss1 and ss2) in brain were showed higher expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…Politis, Butts, and Tomkiewicz () found that 12:12 hr light/dark low‐intensity red light conditions (10 lux and 0.2 μmol m −2 s −1 ) enhanced the survival of European eel larvae, while the hatching rate of zebrafish was highest under blue or violet light, and total body length at 30 dph was greatest under blue, white or violet light (Villamizar, Vera, Foulkes, & Sánchez‐Vázquez, ). When tiger puffers were reared under different light conditions (blue, green or red) for 8 weeks, somatic larval growth was better under green light conditions (Kim, Hur, Hur, Lee, & Lee, ), while tiger puffers reared under red light showed slower growth than the other experimental groups. Additionally, blue light had a negative impact on rainbow trout growth performance (Karakatsouli et al, ), while yellow light increased the mean weight of these fish (Heydarnejad, Parto, & Pilevarian, ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Politis, Butts, and Tomkiewicz () found that 12:12 hr light/dark low‐intensity red light conditions (10 lux and 0.2 μmol m −2 s −1 ) enhanced the survival of European eel larvae, while the hatching rate of zebrafish was highest under blue or violet light, and total body length at 30 dph was greatest under blue, white or violet light (Villamizar, Vera, Foulkes, & Sánchez‐Vázquez, ). When tiger puffers were reared under different light conditions (blue, green or red) for 8 weeks, somatic larval growth was better under green light conditions (Kim, Hur, Hur, Lee, & Lee, ), while tiger puffers reared under red light showed slower growth than the other experimental groups. Additionally, blue light had a negative impact on rainbow trout growth performance (Karakatsouli et al, ), while yellow light increased the mean weight of these fish (Heydarnejad, Parto, & Pilevarian, ).…”
Section: Discussionmentioning
confidence: 95%
“…Several previous studies also tried to clarify the mechanism whereby light affect the teleost fish growth performance (Kim et al, ; Shin, Lee, & Choi, ; Villamizar et al, ). Growth, food intake and digestion are related to specific behavioural rhythms, including reproduction, with pineal hormones (such as melatonin) being the assumed regulators of these mechanisms (Underwood, ; Zachmann, Falcon, Knijff, Bolliet, & Ali, ).…”
Section: Discussionmentioning
confidence: 99%
“…The long‐term rearing of tiger puffer Takifugu rubripes (Kim et al . ) for 8 weeks showed that the growth of fish under green and blue rays of the spectrum was higher than under red light. At the same time, this dependence became evident from the 4th week of the experiment until the end of the experiment.…”
Section: Growthmentioning
confidence: 95%
“…Interesting results were obtained in a study of the environmental colour impact on growth and the associated hormonal processes in Takifugu rubripes (Kim et al . ). It showed that green light induces the growth of individuals and at the same time reduces the expression of growth hormone‐inhibiting hormone (GHIH).…”
Section: Probable Mechanisms Of the Effect Of Colour On Growth (Stresmentioning
confidence: 97%
“…Recently, several studies were investigated on the effect of light spectrum on reproductive and growth performance ( Shin et al, 2014 ; Kim et al, 2016 ). According to studies on gold fish ( Carassius auratus ), the gene expression of GnRH and GtH as well as Kisspeptin (known to be a major regulator of reproduction and puberty initiation) increased at the green spectrum compared to that at the red spectrum.…”
Section: Discussionmentioning
confidence: 99%